KARAKTERISTIK ENDAPAN LATERIT NIKEL DAN UNSUR TANAH JARANG DI DAERAH PULAU GEBE, HALMAHERA TENGAH, MALUKU UTARA : CHARACTERISTICS OF NICKEL LATERITE DEPOSITS AND RARE EARTH ELEMENTS IN GEBE ISLAND, CENTRAL HALMAHERA, NORTH MALUKU - Rabbani Rafif Abidin; Very Susanto; Sulaeman; Hartaja M. Hatta Wicaksono (Buletin Sumber Daya Geologi, 2022)
Nickel laterite is a product of weathering of ultramafic rocks that have an abundance of olivine and orthopyroxene minerals. Geology in the Gebe Island, Central Halmahera Regency, North Maluku Province is composed of limestone, which is equivalent to the Waigeo Formation which has an inconsistent relationship with the underlying ultramafic rocks as carriers of laterite nickel deposits. Weathering of ultramafic rocks produces a different profile and character of laterite nickel. This study aims to determine the characteristics of laterite and rocks from the area and to determine the characteristics of rare earth elements. Based on the results of the study, it is known that laterite nickel carriers in the area are dunite. Laterite nickel deposit profile on the island consists of red limonite, yellow limonite, and saprolite. The red limonite zone is characterized by a relatively high Fe2O3 content and a strong degree of lateritization; the yellow limonite zone is characterized by a relatively high Al2O3 content and a weak to strong lateritization degree; the saprolite zone is characterized by a relatively high MgO and SiO2 content. In general, laterite Ni deposits in the study area show relative enrichment of REE to bedrock and LREE content is more abundant than HREE content. Based on the spearman correlation, the main controller of LREE(La-Eu) and HREE(Gd-Lu) enrichment is Fe mineral with the spearman coefficient value between LREE(La-Eu) and HREE(Gd-Lu) with Fe2O3 is 0,64-0,83. While the main controller of Sc enrichment is Al mineral with the spearman coefficient value between Sc and Al2O3 being 0,59.